Development a quantitative method for the determination of misoprostol acid in human serum - López, Luis A. (2017)
Was made an experimental study with longitudinal design to develop a qualitative and quantitative method to determine misoprostol ester through its metabolite misoprostol acid in serum samples. An ultraperformance liquid chromatograph equipment with a mass-mass detector (UPLC MS-MS) was used, obtaining peaks at 2,2 minutes of chromatographic running and concentrations between 3,1 and 18,4 ppb.